2022
DOI: 10.3390/jcdd9100358
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Different Nutritional Indices Combined with the GRACE Score in Predicting the Risk of Long-Term Death in Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention

Abstract: Nutritional status is associated with prognosis in acute coronary syndrome (ACS) patients. Although the Global Registry of Acute Coronary Events (GRACE) risk score is regarded as a relevant risk predictor for the prognosis of ACS patients, nutritional variables are not included in the GRACE score. This study aimed to compare the prognostic ability of the Geriatric Nutritional Risk Index (GNRI) and Prognostic Nutritional Index (PNI) in predicting long-term all-cause death in ACS patients undergoing percutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Twenty studies were eligible for full-text analysis. Finally, 15 were eligible for this review ( 14 18 , 21 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty studies were eligible for full-text analysis. Finally, 15 were eligible for this review ( 14 18 , 21 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…PNI was initially described to check the nutritional status of gastrointestinal surgery, but over the years it has been recognized as an important prognostic factor in several cancers (11)(12)(13). Over the past years, many studies have also used PNI to predict prognosis of CAD patients but with inconsistent results (14)(15)(16)(17)(18). However, no systematic review has been attempted to summarize the available evidence.…”
mentioning
confidence: 99%
“…The exclusion criteria for spinal tuberculosis patients were as follows: (1) patients with active tuberculosis of the lung and other parts; (2) lack of clinical data; (3) patients with serious medical diseases such as diabetes; (4) immune dysfunction or some disease affecting the function of the immune system or need to take long-term drugs to inhibit the function of the immune system. The selection of exclusion criteria takes full account of the potential impact on miRNA expression 23 .…”
Section: Subjectsmentioning
confidence: 99%
“…The Prognostic Nutritional Index (PNI), which combines two nutritional markers, namely serum albumin and total lymphocyte count, has been validated in evaluating the nutritional and inflammatory status of critically ill patients to predict outcomes such as the length of hospital stay, postoperative delirium, and mortality and morbidity in cancer and non-cancer surgical settings 8 13 . Although a low PNI score (i.e., poor nutritional status) has been shown to be related to increased morbidity and mortality in patients with malignancy, its role as an indicator of the long-term outcome in patients receiving coronary interventions for ACS remains controversial 6 , 7 , 14 16 . In a recent study, Chen et al demonstrated the potential benefits of incorporating PNI into the Global Registry of Acute Coronary Events (GRACE) score for the prediction of long-term all-cause mortality in patients diagnosed with ACS 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Although a low PNI score (i.e., poor nutritional status) has been shown to be related to increased morbidity and mortality in patients with malignancy, its role as an indicator of the long-term outcome in patients receiving coronary interventions for ACS remains controversial 6 , 7 , 14 16 . In a recent study, Chen et al demonstrated the potential benefits of incorporating PNI into the Global Registry of Acute Coronary Events (GRACE) score for the prediction of long-term all-cause mortality in patients diagnosed with ACS 16 . In contrast, Basta et al 7 utilized the Controlling Nutritional Status (CONUT) score as a measure of nutritional status and observed that it exhibited a more robust and significant association with all-cause mortality than the PNI in patients with ST-segment elevation myocardial infarction (STEMI).…”
Section: Introductionmentioning
confidence: 99%